Exploring lactic acid bacteria diversity for better fermentation of plant-based dairy alternatives - Mark S. Turner; Claus Heiner Bang-Berthelsen; Sangeeta Prakash; Anders Peter Wätjen; Wenkang Huang (Microbiology Australia, 2022)
Plant-based foods have risen in popularity in recent years including a number of dairy alternative products. Fermentation has the potential to support the development of innovative plant-based foods with enhanced flavour, texture and nutritional quality. Lactic acid bacteria (LAB) have been used for thousands of years to carry out fermentation of a wide variety of food substrates through production of organic acids and flavour compounds. However, LAB strains used in dairy fermentations are commonly found to be suboptimal in their metabolism of plant substrates, so efforts to identify alternative strains are needed. We provide an overview of the plant-based milk alternative category and explore screening approaches (including citizen-science efforts) to identify new LAB that hold potential in acidification and flavour formation of plant-based substrates.